Collaboration Among Schools, Families, and the Community in Supporting Inclusive Education for Students with ADHD: A Literature Review - Anggun Permata Hati; Sekar Auwalia Riswana; Lilis Suhaila Nur Aini (GRAB KIDS: Journal of Special Education Need, 2026)
Inclusive education for students with Attention Deficit Hyperactivity Disorder (ADHD) requires comprehensive support, not only from schools but also from families and the community as the broader social environment. Several studies emphasize that collaboration between classroom teachers and special education teachers supported by school policies and understanding from the surrounding community can enhance the effectiveness of inclusive education. Thus, integrated cooperation among schools, families, and the community serves as the foundation for achieving optimal inclusive education for students with ADHD. This study employed a Systematic Literature Review (SLR) approach, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Various studies have examined collaboration between schools, families and professionals in inclusive education, the involvement of the community as part of the educational support system for pupils with ADHD has not yet been widely discussed. This literature review concludes that collaboration among schools, families, and communities is a key determinant of the success of inclusive education for students with ADHD.